Innovations of Islamic Early Childhood Education in Indonesia During the Pandemic - Indhar Wahyu Wira Harjo; Dewi Puspita Rahayu (Nadwa: Jurnal Pendidikan Islam, 2021)
Learning innovation for early childhood during a pandemic is an essential issue to be studied. Learning innovation needs to be contextualized around distance learning as one of the learning models during the Pandemic. This study maps the  problemsin implementing long-distance learning for early childhood. The data in this study came from interviews with principals, teachers, and parents of students who were directly involved with children's learning during the Pandemic. The study results showed that the problems that occur in online learning include technical and substantive aspects. These problems have become a catalyst for school actors to innovate in collaboration between schools and parents to implement learning activities. In addition, the innovation also includes policy aspects related to the implementation of learning activities at the school level. This study recommends that studies on the effectiveness and efficiency of learning involving parents of students and face-to-face on a limited basis need to be studied further to gain a deeper understanding of learning innovations during the Pandemic.